Sistem Informasi Kepegawaian Pada Pt Xyz Berbasis Website - Savitri, Nabila; Mardiani, Mardiani (MDP Student Conference, 2024)
PT XYZ company is a company operating in the development sector which focuses on the world of residential property and shophouses. It currently has approximately 40 employees divided into several divisions. Currently, PT XYZ has difficulties in collecting data, storing and managing employee data which is still inefficient. Based on this, the website-based personnel information system at XYZ Company was created with the aim of assisting several parties in carrying out existing work procedures, such as collecting employee data, recording employee permits and leave and several other procedures. The method used in creating this system is the RUP (Rational Unified Process) method, which is a development method that is carried out repeatedly. The related system design was carried out using the Visual Studio Code, MySQL and Laravel applications as a framework using the PHP programming language. The system created is expected to help companies manage employee data in the company.